2015
DOI: 10.1038/srep10095
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Novel Sesquiterpene Synthases from Indian Sandalwood, Santalum album

Abstract: Indian Sandalwood, Santalum album L. is highly valued for its fragrant heartwood oil and is dominated by a blend of sesquiterpenes. Sesquiterpenes are formed through cyclization of farnesyl diphosphate (FPP), catalyzed by metal dependent terpene cyclases. This report describes the cloning and functional characterization of five genes, which encode two sesquisabinene synthases (SaSQS1, SaSQS2), bisabolene synthase (SaBS), santalene synthase (SaSS) and farnesyl diphosphate synthase (SaFDS) using the transcriptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 47 publications
(52 reference statements)
1
49
0
1
Order By: Relevance
“…Six genes were predicted to encode SS (SaT03849-R1, SaT03530-R1, SaT22220-R1, SaT22217-R1, SaT23033-R1, and SaT22976-R1). We performed a BLASTP search of the predicted proteins corresponding to genes identified in our study with previously characterized genes (Jones et al, 2011;Srivastava et al, 2015). We found that SaT22220-R1, SaT22217-R1, SaT02056-R1, SaT23033-R1, and SaT22976-R1 genes were highly similar (greater than 85%) to SaSQS1 (KJ665776), SaSQS2 (KJ665777), SaFDS (KF011939), SaBS (KJ665778), SaSS (KF011938), and SaSSy (HQ343276) (Supplemental Fig.…”
Section: Santalol Biosynthesis Pathway In Sandalwoodmentioning
confidence: 88%
See 1 more Smart Citation
“…Six genes were predicted to encode SS (SaT03849-R1, SaT03530-R1, SaT22220-R1, SaT22217-R1, SaT23033-R1, and SaT22976-R1). We performed a BLASTP search of the predicted proteins corresponding to genes identified in our study with previously characterized genes (Jones et al, 2011;Srivastava et al, 2015). We found that SaT22220-R1, SaT22217-R1, SaT02056-R1, SaT23033-R1, and SaT22976-R1 genes were highly similar (greater than 85%) to SaSQS1 (KJ665776), SaSQS2 (KJ665777), SaFDS (KF011939), SaBS (KJ665778), SaSS (KF011938), and SaSSy (HQ343276) (Supplemental Fig.…”
Section: Santalol Biosynthesis Pathway In Sandalwoodmentioning
confidence: 88%
“…Currently, large-scale transcriptomic data sets are available for sandalwood (Diaz-Chavez et al, 2013;Srivastava et al, 2015;Zhang et al, 2015Zhang et al, , 2017Celedon et al, 2016) and Santalum spicatum (Moniodis et al, 2015). Most of these genomic resources have been utilized to identify genes involved in sandalwood oil biosynthesis, cold stress response, and the hemiparasitic nature of its roots.…”
mentioning
confidence: 99%
“…45 This essential oil comprises a blend of sesquiterpene hydrocarbons and alcohols and exhibits useful antimicrobial, antiinflammatory, and antitumor properties. 4648 SASQS1 and SASQS2 each contain 566 residues and are related by 80% amino acid sequence identity; based on amino acid sequence analysis, each enzyme adopts the characteristic αβ domain architecture 49,50 of a plant sesquiterpene cyclase.…”
Section: Discussionmentioning
confidence: 99%
“…The plasmids were transferred into E. coli Rosetta DE3α cells. The cells carrying the plasmids FPPS‐pRSETB , ECS‐pET28a , and FPPS‐ECS‐pET32a were grown in 1 L Terrific broth (Hi‐media, India), with ampicillin (100 µg/mL) and chloramphenicol (34 µg/mL), at 37°C. At OD 600 of ∼0.8, IPTG was added to the final concentration of 1 mM.…”
Section: Methodsmentioning
confidence: 99%
“…The plasmids were transferred into E. coli Rosetta DE3 cells. The cells carrying the plasmids FPPS-pRSETB [29], ECS-pET28a [28], and FPPS-ECS-pET32a were grown in 1 L Terrific broth (Hi-media, India), with ampicillin (100 μg/mL) and chloramphenicol (34 μg/mL), at 37 • C. At OD 600 of ∼0.8, IPTG was added to the final concentration of 1 mM. The cells were harvested after overnight incubation at 16 • C by centrifugation at 6500 × g for 10 min at 16 • C, and pellets were resuspended in 15 mL lysis buffer (50 mM Tris/HCl pH 7.8, containing 300 mM NaCl and 10% glycerol, 5 mM imidazole, 1 mM dithiothreitol), lysozyme (1 mg/mL), CHAPS (0.01%), and Triton X 100 (0.1%) were added.…”
Section: Optimization Of Expression and Purification Of The Recombinamentioning
confidence: 99%